Basic DNA and RNA protocols - Harwood, Adrian J (Humana Press, 1996)
MRC Laboratory, London, U.K. Manual of core techniques in molecular genetics, including DNA and RNA analysis, gene cloning, sub cloning, PCR, DNA sequencing, and site-directed mutagenesis and protein expression. 54 contributors, 20 U.S. Plastic comb spiral binding.
Methods in molecular biology ; Vol. 58
Keywords: klinické laboratorní techniky; nukleové kyseliny; referenční knihy; Clinical Laboratory Techniques; Nucleic Acids; biologie; RNA; Laboratorní technika; DNA; Reference Books; biochemie